Examining the effectiveness of online resources in developing English as a Foreign Language (EFL) reading skills autonomously - Yahya Bouhafa; Shelby R. Hochberg (Institut Agama Islam Negeri Palopo, 2021)
The purpose of this mixed methods study is to investigate the effectiveness of online resources in developing English as a Foreign Language (EFL) reading skills autonomously among undergraduate students at the Faculty of Letters and Humanities Fes-Agdal as a representative of the socio-cultural and higher education system of Morocco. The sample consisted of an experimental group and a control group. The experimental group consisted of 120 students that were exposed to three main online tools (Newsela.com, mrnussbaum.com, and rewordify.com) and virtual meetings and instruction provision using Facebook. The control group consisted of 120 students that benefited only from the university’s regular reading courses. The experimental intervention period was followed by interviews with a sample of 25 students from both groups providing a qualitative perspective. The overall results show that online resources had a positive effect on the development of metacognitive skills. Students tended to appreciate the inclusion of online resources in the classroom without devaluing the role of their EFL teacher – the students did not expect online resources to fully replace the role of their teachers.